Bureaucracy-Legislature dynamics in policy making the case of the foreign investment act of the Philippines - Brillo, Bing Baltazar C. (2014)
Time and again scholars have interpreted policy making in the Philippine using the weak state framework-Philippine policy is characterized by a homegenous-controlling legislature and an ineffective-subservient bureaucracy. The legislation of the foreign investment act, however, suggests that a different dynamics existed between the bureaucracy and the legislature. First, the bureaucracy and legislature were not homogenous. Despite having ideological unity, the government agencies and the legislative bodies took varying stances during the legislative deliberation. Second, the bureaucracy was influential in policy making. The influence of the bureaucratic agencies was evident throughout the legislative proceedings, from the agenda setting to the policy outcome. Third, the legislature was reactive to the bureaucratic inputs in policy legislation. The bureaucratic proposals and opinions were readily accepted, heavily relied on and served as the basis for the responses of the legislative bodies. Overall, the case of the making of foreign investment law reveals that, although lawmaking is technically the domain of the legislature, the bureaucracy holds sway in policy making..
Keywords: Foreign Investment Act